2017
DOI: 10.1111/nmo.13247
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal esophageal acid exposure on high‐dose proton pump inhibitor therapy is common in systemic sclerosis patients

Abstract: Abnormal esophageal acid exposure despite high-dose PPI therapy was common among patients with SSc. The lack of increased reflux episodes in the SSc patients, and longer bolus clearance times and lower nocturnal impedance, supports ineffective clearance as the potential mechanism. Systemic sclerosis patients may require adjunctive therapies to PPIs to control acid reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A PPI daily dose is started 30-60 min before the first meal of the day, and the dose is increased to twice daily if the response is partial or there are nocturnal symptoms[ 55 ]. A matched retrospective case-control study in which 38 patients with SSc and 38 controls who underwent esophageal pH-impedance with double-dose PPI were included found a higher AET ≥ 4.5% (61% cases vs 18% controls P < 0.001), higher median bolus clearance, and lower mean nocturnal baseline impedance, which would support ineffective esophageal clearance as the potential mechanism, for which additional therapies with PPIs to control acid reflux should be considered in these patients[ 56 ]. A clinical trial that included SSc patients with GERD who had a partial response to PPIs randomized to domperidone and alginic acid found that after treatment with both drugs, the severity and frequency of symptoms and quality of life improved; however, 17% of the patients did not respond to the combination treatment[ 57 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…A PPI daily dose is started 30-60 min before the first meal of the day, and the dose is increased to twice daily if the response is partial or there are nocturnal symptoms[ 55 ]. A matched retrospective case-control study in which 38 patients with SSc and 38 controls who underwent esophageal pH-impedance with double-dose PPI were included found a higher AET ≥ 4.5% (61% cases vs 18% controls P < 0.001), higher median bolus clearance, and lower mean nocturnal baseline impedance, which would support ineffective esophageal clearance as the potential mechanism, for which additional therapies with PPIs to control acid reflux should be considered in these patients[ 56 ]. A clinical trial that included SSc patients with GERD who had a partial response to PPIs randomized to domperidone and alginic acid found that after treatment with both drugs, the severity and frequency of symptoms and quality of life improved; however, 17% of the patients did not respond to the combination treatment[ 57 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…6,7 Suspicion of GERD may be further heightened in the presence of other co-morbid conditions which can augment reflux physiology such as a hiatal hernia, central obesity, or connective tissue disorders (ie, scleroderma). [8][9][10][11] Further, initial evaluations should assess for symptom specific anxiety, psychological comorbidity and hypervigilance, as well as the potential of non-GERD disorders, such as rumination, a belching disorder, eosinophilic esophagitis, or achalasia.…”
Section: Gauging Probability Of Objective Gerdmentioning
confidence: 99%
“…81 86 Although the oesophagus is not always affected in patients with systemic sclerosis, the majority of patients with oesophageal involvement is found to have aperistalsis, which is a risk factor for postoperative dysphagia also in patients without scleroderma. [87][88][89] 8. Patients with concomitant functional disorders such as dyspepsia and IBS are good candidates for antireflux surgery, only if symptoms can be attributed to reflux.…”
Section: Clinical Presentation and Comorbiditiesmentioning
confidence: 99%